SARS-CoV-2 entry sites are present in all structural elements of the human glossopharyngeal and vagal nerves: Clinical implications - Lynn Vitale-Cross; Ildiko Szalayova; Aiden Scoggins; Miklos Palkovits; Eva Mezey (EBioMedicine, 2022)
Summary: Background: Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infections result in the temporary loss of smell and taste in about one third of confirmed cases. Methods: We used immunohistochemistry to confirm the presence of ACE2, NRP1 and TMPRSS2 in two cranial nerves (IX and X) that mediate taste where they leave/join the medulla. Samples from three (two paraffin embedded and one frozen) postmortem samples were studied (facial (VII) nerve was not available). We also performed immunohistochemistry using the same antibodies in two human cell lines (oligodendrocytes and fibroblasts), and we isolated RNA from one nerve and performed PCR to confirm the presence of the mRNAs that encode the proteins visualized. Findings: All three of the proteins (ACE-2, NRP1 and TMPRSS2) required for SARS-CoV-2 infections appear to be present in all cellular components (Schwann cells, axons, vascular endothelium, and connective tissue) of the human IXth and Xth nerves near the medulla. We also found their mRNAs in the nerve and in human oligodendrocytes and fibroblasts which were stained by antibodies directed at the three proteins examined. Interpretation: Infection of the IXth and Xth nerves by the SARS-CoV-2 virus is likely to cause the loss of taste experienced by many Covid patients. Migration of the virus from the oral cavity through these nerves to brainstem respiratory centers might contribute to the problems that patients experience. Funding: This study was supported by the Intramural Research Program of the National Institute of Dental and Craniofacial Research (NIDCR), NIH (intramural project no. ZDE000755-01), and the Human Brain Tissue Bank, Semmelweis University, Budapest, Hungary from the Hungarian Brain Research Program (2017-1.2.1-NKP-2017-00002).